Factors Impacting Initial Arthroscopy Performance and Skill Progression in Novice Trainees - Cychosz, Chris C. (Iowa Orthop J, 2019)
BACKGROUND: Arthroscopy is one of the cornerstone skills learned during orthopaedic residency training. Previous studies have attempted to identify characteristics of arthroscopy naive individuals leading to superior initial arthroscopic performance with conflicting findings. Furthermore, other virtual reality simulator studies consisting of beginner trainees, have noted that certain individuals fail to progress at the rate of their peers despite rigorous training. Therefore the purpose of this study was to 1) identify trainee characteristics that may have an impact on initial arthroscopy skill and performance and 2) identify trainee characteristics affecting their ability to improve through training on an arthroscopy simulator. METHODS: Forty-three medical students with no prior arthroscopy experience performed a diagnostic knee arthroscopy using an anatomic virtual reality simulator. Prior to the procedure, information was collected about each participant regarding various demographics, sports involvement, hand dominance, specialty interest, 3-D video game use and experience assisting in the operating room. Their baseline performance was measured using the following outcomes: time (seconds), camera path length (CPL) (centimeters), and an overall composite score. A subgroup consisting of 22 students underwent training with a non-anatomic virtual arthroscopy simulator consisting of a series of 5 self-guided modules after their initial knee scope. This group was retested using the same diagnostic knee scope one to two weeks later. Participant background characteristics were correlated with initial performance on the knee scope and the change from the first to second knee scope in the sub-group that completed the training. RESULTS: At the time of the initial diagnostic knee arthroscopy, performance was most strongly correlated with how often an applicant currently plays video games and how often they have played video games in the past. However, this was only a weak correlation (r= 0.29 and 0.24, respectively). Interestingly, students pursuing a non-surgical residency outperformed those interested in a surgical specialty in all outcome measurements at baseline, although this did not reach a level of significance. Year of training in medical school, age, hand dominance, current or past participation in sports requiring hand-eye coordination, and number of surgical cases they have assisted in for did not influence initial performance. Participants that have operated another type of scope (e.g. bronchoscopy, laparoscopy) in the past showed a trend towards higher performance in composite score (21.6 vs 14.9, p = 0.07), although this did not reach a level of significance. Regarding the change in performance of those that completed the non-anatomic training prior to the second knee scope, change in time to complete the procedure was significantly different between participants in different years of medical school. Fourth year medical students improved by an average of 421 seconds compared to 98 seconds, 127, and 140 seconds for the other classes, p = 0.02. Those who have regularly participated in sports requiring hand eye coordination in the past improved their time (182 vs 78 seconds, p = 0.0245) and camera path length (96 vs 31 cm, p = 0.0372) significantly more than those were not involved in sports. DISCUSSION AND CONCLUSIONS: Our study demonstrates that baseline arthroscopy performance correlates most highly with 3D video game experience. The ability of trainees to learn arthroscopy using a virtual reality simulator appears to be influenced more by those who have regularly participated in sports requiring hand eye coordination rather than video game use. Level of Evidence: III